PLXNB1 mutations in the etiology of idiopathic hypogonadotropic hypogonadism. (16th February 2022) - Welch, Bradley A.; Cho, Hyun‐ju; Ucakturk, Seyit Ahmet; Farmer, Stephen Matthew; Cetinkaya, Semra; Abaci, Ayhan; Akkus, Gamze; Simsek, Enver; Kotan, Leman Damla; Turan, Ihsan; Gurbuz, Fatih; Yuksel, Bilgin; et al.
Abstract: Idiopathic hypogonadotropic hypogonadism (IHH) comprises a group of rare genetic disorders characterized by pubertal failure caused by gonadotropin‐releasing hormone (GnRH) deficiency. Genetic factors involved in semaphorin/plexin signaling have been identified in patients with IHH. PlexinB1, a member of the plexin family receptors, serves as the receptor for semaphorin 4D (Sema4D). In mice, perturbations in Sema4D/PlexinB1 signaling leads to improper GnRH development, highlighting the importance of investigating PlexinB1 mutations in IHH families. In total, 336 IHH patients (normosmic IHH, n  = 293 and Kallmann syndrome, n  = 43) from 290 independent families were included in the present study. Six PLXNB1 rare sequence variants (p.N361S, p.V608A, p.R636C, p.V672A, p.R1031H, and p.C1318R) are described in eight normosmic IHH patients from seven independent families. These variants were examined using bioinformatic modeling and compared to mutants reported in PLXNA1 . Based on these analyses, the variant p.R1031H was assayed for alterations in cell morphology, PlexinB1 expression, and migration using a GnRH cell line and Boyden chambers. Experiments showed reduced membrane expression and impaired migration in cells expressing this variant compared to the wild‐type. Our results provide clinical, genetic, molecular/cellular, and modeling evidence to implicate variants in PLXNB1 in the etiology of IHH. Abstract : We provide clinical, genetic, molecular/cellular, and modeling evidence to implicate variants in PLXNB1 signaling in the etiology of idiopathic hypogonadotropic hypogonadism. These studies add to the growing number of semaphorin signaling molecules in GnRH ontogeny, and thus mutations in the pathogenesis of pubertal failure.